An Analysis of Applied Buddhist Metaphysics in Societal Context - Prak, Samphose; Wongpornpavan, Chakkapan; Keo, Ratanak (วารสารศิลปะและวัฒนธรรมลุ่มแม่น้ำมูล, 2024)
The objective of this academic article aims to present, an analysis of Applied Buddhist Metaphysics in Society, is 1) what does Buddhist metaphysics mean for society and its source 2) how to get benefit from applied Buddhist metaphysics in the societal context 3) and an analysis of Buddhist metaphysics in framework of critical thinking.